Embodied metacognition as strengthened functional connection between neural correlates of metacognition and dance in dancers: exploring creativity implications - Yang, Ching-Ju; Yu, Hsin-Yen; Hong, Tzu-Yi; Cheng, Li-Kai; Li, Wei-Chi; Yeh, Tzu-Chen; Chen, Li-Fen; Hsieh, Jen-Chuen (Frontiers in Human Neuroscience, 2024)
Introduction: Dance education fosters embodied metacognition, enhancing student's creativity. This study examines the crucial role of functional connectivity (FC) between the neural correlates of metacognition (NCM) and dance (NCD) as the neurological foundation for dancers' embodied metacognition. The investigation also explores whether these consolidated FCs inform the general creativity in dancers. Methods: The research involved 29 dancers and 28 non-dancer controls. The study examined resting-state connections of the NCM through seed-based FC analysis. Correlation analyses were employed to investigate the connections between the targeted NCM-NCD FCs, initiated from the a priori NCM seed, and general creativity. Results: Dancers demonstrated heightened FC between NCM and NCD compared to non-dancer controls.The targeted regions included the putamen, globus pallidus, posterior cerebellum, and anterior insula of NCD.The dancers exhibited higher originality scores. In dancers, the enhanced FC showed a negative correlation with originality and a positive correlation with flexibility. Conversely, the controls exhibited no significant correlations. Discussion: Extended dance training enhances the NCM-NCD connection signifying embodied metacognition. This interconnectedness may serve as the neural predisposition for fostering general creativity performance in dancers. Dancers with heightened levels of originality could leverage the relatively weaker NCM-NCD FCs to facilitate better integration and coordination of creative cognitive processes. Our findings suggest that the consolidated functional connections as sculpted by domain-specific training may inform general creativity.